Disentangling the importance of the precautionary saving motive - Arthur Kennickell; Annamaria Lusardi (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We evaluate the importance of the precautionary saving motive by relying on a direct question about precautionary wealth from the 1995 and 1998 waves of the Survey of Consumer Finances. In this survey, a new question has been designed to elicit the amount of desired precautionary wealth. This allows us to assess the amount of precautionary accumulation and to overcome many of the problems of previous works on this topic. We find that a precautionary saving motive exists and affects virtually every type of household. However, precautionary savings account for only 8 percent of total wealth holdings. Even though this motive does not give rise to large amounts of wealth, particularly for young and middle-age households, it is particularly important for two groups: older households and business owners. Overall, we provide strong evidence that we need to take the precautionary saving motive into account when modeling saving behavior.
urn:nbn:de:hebis:30-29433
Keywords: D91; E21; C21; 330; Risk; Buffer-stock Models of Saving; Old Cohorts Wealth; Business Owners Wealth